Sodium-dependent magnesium uptake by ferret red cells. - Flatman, P W (1991)
1. Magnesium uptake can be measured in ferret red cells incubated in media containing more than 1 mM-magnesium. Uptake is substantially increased if the sodium concentration in the medium is reduced. 2. Magnesium uptake is half-maximally activated by 0.37 mM-external magnesium when the external sodium concentration is 5 mM. Increasing the external sodium concentration increases the magnesium concentration needed to activate the system. 3. Magnesium uptake is increased by reducing the external sodium concentration. Uptake is half-maximum at sodium concentrations of 17, 22 and 62 nM when the external magnesium concentrations are 2, 5 and 10 mM respectively. 4. Replacement of external sodium with choline does not affect the membrane potential of ferret red cells over a 45 min period. 5. Magnesium uptake from media containing 5 mM-sodium is inhibited by amiloride, quinidine and imipramine. It is not affected by ouabain or bumetanide. Vanadate stimulates magnesium uptake but has no effect on magnesium efflux. 6. When cell ATP content is reduced to 19 mumol (1 cell)-1 by incubating cells for 3 h with 2-deoxyglucose, magnesium uptake falls by 50% in the presence of 5 mM-sodium and is completely abolished in the presence of 145 mM-sodium. Some of the inhibition may be due to the increase in intracellular ionized magnesium concentration ([Mg2+]i) from 0.7 to 1.0 mM which occurs under these conditions. 7. Magnesium uptake can be driven against a substantial electrochemical gradient if the external sodium concentration is reduced sufficiently. 8. These findings are discussed in terms of several possible models for magnesium transport. It is concluded that the majority of magnesium uptake observed in low-sodium media is via sodium-magnesium antiport. A small portion of uptake is through a parallel leak pathway. It is believed that the antiport is responsible for maintaining [Mg2+]i below electrochemical equilibrium in these cells at physiological external sodium concentration. Thus in ferret red cells the direction of magnesium transport can be reversed by reversing the sodium gradient.